Peran Hadis Riwayah dan Dirayah dalam verifikasi dan pemahaman hadis: Pendekatan komprehensif terhadap studi hadis - Faiz, Moh (Maliki Interdisciplinary Journal, 2024)
Hadith, as the second source of Islamic law after the Quran, encompasses two crucial aspects in its study: hadith riwayah and hadith dirayah. This research aims to analyze the differences and relationships between these two aspects in hadith studies. Hadith riwayah focuses on the process of narration and transmission of hadith from Prophet Muhammad PBUH to the last narrator, including the examination of chains of transmission (sanad) and textual content (matn). Meanwhile, hadith dirayah involves a deeper study of hadith understanding methodology and criticism, encompassing the analysis of the authenticity of both sanad and matn, as well as the contextual understanding of hadith content. These two aspects complement each other in understanding and verifying hadith authenticity. Through a descriptive-analytical approach, this research demonstrates that the integration of hadith riwayah and dirayah is essential in developing a comprehensive understanding of hadith, as well as ensuring accuracy in deriving Islamic laws and their application in contemporary Muslim life.